(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Leadership is vital in shaping an organisation’s long-term success, especially in the current global climate where sustainable business practices are increasingly prioritised. Modern leadership extends beyond vision and communication, requiring adaptability to societal and environmental challenges. Purpose: There is a growing need for leadership that drives sustainable performance. This study intends to explore the leadership style that helps improve sustainable performance using quantitative and qualitative methods. Using a systematic literature review, it aims to establish the relationship between leadership style (LS) and sustainable performance (SP). Methods: Manual in-depth review and network analysis were applied. Current research utilised a sample of 39 peer-reviewed articles from 2010 to 2025 from the Scopus database. The study employed the PRISMA (Preferred reporting items for systematic review and thematic analysis) technique. Findings: After the detailed analysis and synthesis of the sample paper, the author noticed that responsive and transformative leadership was seen as the most preferred, while social exchange theory and upper echelon theory were the two theories used in most of the sample articles. This study synthesizes the effect of leadership upon SP using the author’s end result in the analysed paper. Conclusion: This research contributes towards establishing a connection between leadership and sustainable performance from a holistic perspective using methodologically rigorous and multi-layered analysis. The framework of this study not only manifests upon discussion and presentation of outcomes but also contributes to future researchers to study leadership and sustainable performance in a more comprehensive and integrated way, which can establish an ethically successful and lucrative form of leadership. Keywords: Leadership, Sustainable performance, Innovation, Social exchange theory.